Symbiotic yogurt and flour of passion fruit (Passiflora edulis) as nutritional support in people with hyperglycemia - Osso Arriz, Oscar Otilio (2019)
The objective is that symbiotic yogurt can be elaborate with Passiflora edulis (passion fruit) flour as nutritional support in people with type 2 hyperglycemia. The methods were experimental design, longitudinal cut, because an evaluation process was developed against a phenomenon that was being carried out, not observing. The monitoring of hyperglycemia was measured at the beginning and monthly in two groups that were compared: Group of cases that were given a daily amount of symbiotic yogurt with passion fruit flour and diet, while the other group (control) received only diet, both for 3 months. The results were that the treatment with a dose of 500 ml per day produced positive effects in the reduction between 8 % and 9 % of the quantitative values of hyperglycemia, with significant variation (p <0.05) during the 3 months of treatment, with greater effectiveness than in the control group (p = 0.110> 0.05). The product has good acceptance compared to natural yogurt (p = 0.194> 0.05). The conclusions are that there is interaction of diet and the reduction of type 2 hyperglycemia (0.000 <0.05), however, it is statistically shown that it is higher when it is associated with the consumption of symbiotic yogurt with passion fruit flour. Contributes to a healthy diet complementary to the diet as nutritional support in type 2 hyperglycemia.